The aphrophorid spittlebugs of Iran (Hemiptera: Cercopoidea: Aphrophoridae) - Mozaffarian, Fariba; Wilson, Michael R. (Zootaxa, 2015)
An annotated list of Aphrophoridae of Iran is provided, based on examination of specimens housed in the Hayk Mirzayans Insect Museum (Iran) and the National Museum of Wales, Cardiff (UK) and on previously published records. Ten species are now recorded from Iran. An identification key to the genera and species is provided, with illustrations and together with distributions. The subgenus Philaenus (Gyrurus) Tischechkin 2013 is recognized as a junior synonym of Mesoptyelus with Mesoptyelus iranicus (Tishechkin, 2013) as a new combination for Philaenus (Gyrurus) iranicus Tishechkin 2013. Paraphilaenus notatus (Mulsant & Rey, 1855) is recorded for the first time from Iran. Philaenus nebulosus Lethierry 1876 (currently Poophilus nebulosus (Lethierry, 1876)) is proposed to be a junior synonym of the widespread species Poophilus costalis (Walker, 1851).